Phenotypic characteristics of Sakub sheep as local livestock genetic resources - ARI DWI NURASIH; MAS YEDI SUMARYADI; CHOMSIATUN NURUL HIDAYAH; ARAS PRASETIYO NUGROHO; AGUSTINAH SETYANINGRUM; IMBANG HARYOKO; PAMBUDI YUWONO; AKHMAD SODIQ (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nurasih AD, Sumaryadi MY, Hidayah CN, Nugroho AP, Setyaningrum A, Haryoko I, Yuwono P, Sodiq A. 2023. Phenotypic characteristics of Sakub sheep as local livestock genetic resources. Biodiversitas 24: 5671-5675. Sakub sheep is an indigenous sheep with a giant body in the Brebes Regency. Phenotypic characterization is important to increase the population and productivity of Sakub sheep. By combining quantitative and qualitative data, this study will provide a comprehensive insight into the phenotypic profile of Sakub sheep. This study determined the quantitative and qualitative phenotypic characteristics of Sakub sheep. The Sakub sheep used were owned by smallholder farmers using the survey method with interview techniques, observation, and direct measurement of livestock. Samples were taken using purposive sampling in Pandansari and Wanareja villages, which have the largest sheep populations and are easily accessible. The sheep used were rams and ewes sheep in the age group of 1-1.5 years (P0), 1.5-2 years (P1), 2-2.5 years (P2), 2.5-3 years (P3). Phenotypic characteristics observed included quantitative characteristics of body size and qualitative characteristics of body morphology. Body size was measured using measuring tape and hanging scales, including Body Weight (BW), Body Length (BL), Whither Height (WH), Chest Girth (CG), Ear Length (EL), And Tail Length (TL). Body morphology includes head color, body color, face profile, and tail shape. Quantitative characters were analyzed using descriptive statistics, and qualitative characters were analyzed descriptively using relative frequency. The results showed quantitative phenotypic characteristics of Sakub sheep at the age of 1-1.5 years; 1.5-2 years; 2-2.5 years, and 2.5-3 years, such as body weight, body length, chest circumference, whither height, ear length, and tail length increased with age. The qualitative phenotypic characteristics of Sakub sheep are having a head and body with a combination of colors but dominant white, a convex head profile, no horns, and a thin and fat tail.